Dibutyl phthalate induced testicular dysgenesis originates after seminiferous cord formation in rats - Nathália L. M. Lara (Nature Portfolio, 2017)
Abstract Administration of dibutyl phthalate (DBP) to pregnant rats causes reproductive disorders in male offspring, resulting from suppression of intratesticular testosterone, and is used as a model for human testicular dysgenesis syndrome (TDS). DBP exposure in pregnancy induces focal dysgenetic areas in fetal testes that appear between e19.5–e21.5, manifesting as focal aggregation of Leydig cells and ectopic Sertoli cells (SC). Our aim was to identify the origins of the ectopic SC. Time-mated female rats were administered 750 mg/kg/day DBP in three different time windows: full window (FW; e13.5–e20.5), masculinisation programming window (MPW; e15.5–e18.5), late window (LW; e19.5–e20.5). We show that DBP-MPW treatment produces more extensive and severe dysgenetic areas, with more ectopic SC and germ cells (GC) than DBP-FW treatment; DBP-LW induces no dysgenesis. Our findings demonstrate that ectopic SC do not differentiate de novo, but result from rupture of normally formed seminiferous cords beyond e20.5. The more severe testis dysgenesis in DBP-MPW animals may result from the presence of basally migrating GC and a weakened basal lamina, whereas GC migration was minimal in DBP-FW animals. Our findings provide the first evidence for how testicular dysgenesis can result after normal testis differentiation/development and may be relevant to understanding TDS in human patients.